Perancangan Visual Aplikasi "info dusun" sebagai Sistem Informasi Masyarakat - Miyosa, Atmaja Septa (Visualita Jurnal Online Desain Komunikasi Visual, 2020)
SmartCity can be started from the village. The visual design of the InfoDusun application is an innovation on a smartphone. The advantage of the InfoDusun application is creates an information system as a process of sharing information on activities so that citizens are able to make better decisions in planning events. The results of the design are icon logo design, login page design and main page design.